STUDY ON STRUCTURE AND MECHINCAL PROPERTIES OF WELD FOR HARDFACING BY RESISTANCE SEAM WELDING - Nguyen Minh Tan; Le Van Thoai; Ngo Thi Thao (Journal of Applied Science and Technology, 2019)
Present paper studies on structure and mechanical properties of metal weld on a C45 shaft by resistance seam welding with C70 steel wire. Nine experiments with different welding parameters were performed to evaluate the welded structure as well as mechanical properties. ARO 72500 welding machine combined with fixtures was used in the experiemental process. Results show that welded microstructure included needle-shaped martensite and rest austenite. In addition, it is observed that bonding between welded and parent metal, and between welded layers after each electric pulse is quite stable through macrostructure. Bonding strength of welding layer with base metal of the shaft reached about 80 ÷ 95% tensile strength of base metal (488N/mm2); while average hardness of all welding specimens was quite large ensuring the hardness requirement of recovery details (45÷55HRC). Besides, wear resistance of welding samples was 1.24 ÷ 1.44 times higher than that of the new shaft made from C45 steel with high-frequency hardening. From obtained results, it is confirmed that the quality of the resistance seam welding method for recovering the shaft with C70 steel wire is relatively good and can be applied to other materials in the future